Wildlife-logging issues in the tropical rain forest. - Universiti Putra Malaysia, Research Management Centre (Research Management Centre, Universiti Putra Malaysia, 2008)
In recent decades, there has been unprecedented growth in the scale and intensity of tropical forest management. Industrial forestry, both directly and indirectly, has wreaked havoc on the wildlife and the ecological integrity of tropical forests. While the mark of human intervention in modern times is quite apparent, forests have in fact been subject to some form of management. The wildlife of forests that we value so highly today is the result of varying intensities of human management over an extraordinarily long period. And the more we study even the most remote forests, the more surprised we are by the sophistication and extent of its management.